A scratch-resistant plastic masterbatch specially used for plastics and preparation method thereof

By introducing magnesium sulfate whiskers and lignin grafts into the plastic masterbatch and adopting specific process steps, the problem of insufficient scratch resistance performance of plastic products in the prior art is solved, and higher scratch resistance performance and service life are achieved.

CN118126456BActive Publication Date: 2025-04-08ZHEJIANG ZHONGPENG ELECTRICAL & MECHANICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410380332.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-30
Publication Date
2025-04-08
Estimated Expiration
2044-03-30

AI Technical Summary

Technical Problem

In the prior art, the scratch resistance of plastic products is poor, which limits their application.

Method used

A method for preparing a special scratch-resistant plastic masterbatch for plastics, including a combination of polypropylene resin, magnesium sulfate whiskers, antioxidants, nucleating agents, fillers, lignin grafts and polyethylene waxes, is used to prepare plastic masterbatch with excellent scratch-resistant properties through process steps such as ball milling, high-speed mixing and twin-screw extrusion.

Benefits of technology

The toughness and impact strength of the plastic masterbatch are improved, and their scratch resistance is significantly improved, making the surface of the made plastic products more scratch-resistant and their service life are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118126456B_ABST
    Figure CN118126456B_ABST
Patent Text Reader

Abstract

The invention discloses a scratch-resistant plastic masterbatch for plastics and a preparation method thereof, which relates to the field of plastic technology and comprises the following components: polypropylene resin, magnesium sulfate whisker, antioxidant, nucleating agent, filler, lignin graft, polyethylene wax; the molecular weight of the polyethylene wax is 3500; the filler is calcium carbonate; the plastic masterbatch prepared by the invention has excellent scratch resistance and can be applied to the field of plastic products prone to scratches to improve their service life. The invention introduces a certain amount of magnesium sulfate whisker, and the introduction of magnesium sulfate whisker can effectively improve the toughness and impact strength of the plastic masterbatch, mainly because it can disperse stress impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastics, in particular to a special scratch-resistant plastic masterbatch for plastics and a preparation method thereof. Background Art

[0002] Plastic products are widely used in people's daily life, including furniture, electrical appliances, decorations, toys and food containers, etc. Plastic products are generally obtained by processing and molding masterbatches.

[0003] Thanks to the strong expansion of market demand, the output of plastic products continues to increase. With the increase in the output of plastic products, the plastic masterbatch industry has also continued to grow, with a growth rate of more than 20% per year.

[0004] Due to the large-scale application of plastic products, the performance requirements for plastic products are constantly increasing, especially in some special occasions, there are special requirements for the scratch resistance of plastic products, that is, the raw material masterbatch to be prepared needs to have corresponding scratch resistance properties.

[0005] The prior art application publication number is CN 112521689 A, a transparent flame retardant plastic masterbatch and a preparation method thereof "The present invention belongs to the technical field of plastics and their preparation, and provides a transparent flame retardant plastic masterbatch and a preparation method thereof. The transparent flame retardant plastic masterbatch is prepared by mixing polypropylene, octabromoether, triphenyl phosphate, antioxidant, ultraviolet absorber and lubricating dispersant. The transparent flame retardant plastic masterbatch of the present invention is prepared by adding octabromoether and phosphate flame retardant to polypropylene to greatly improve the oxidation index of the transparent flame retardant plastic masterbatch of the present invention, thereby achieving PS self-extinguishing flame retardant performance". However, although it has certain flame retardant properties, its scratch resistance is relatively poor, and the surface of the plastic products made from it is not scratch resistant, which limits its application.

[0006] Based on this, a scratch-resistant plastic masterbatch specially for plastics and a preparation method are provided to solve the existing technical problems. Summary of the invention

[0007] The purpose of the present invention is to provide a special scratch-resistant plastic masterbatch for plastics and a preparation method thereof, so as to solve the deficiencies in the prior art.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A scratch-resistant plastic masterbatch specially used for plastics, comprising the following components by weight:

[0010] 80-90 parts of polypropylene resin, 3-5 parts of magnesium sulfate whisker, 1-3 parts of antioxidant, 1-1.8 parts of nucleating agent, 15-24 parts of filler, 5-8 parts of lignin grafted material, 2-2.5 parts of polyethylene wax;

[0011] The molecular weight of the polyethylene wax is 3500;

[0012] The filler used is calcium carbonate.

[0013] As a further technical solution, the preparation method of the lignin grafted material is:

[0014] (1) First, an organic solvent lignin and 2-bromoisobutyryl bromide are mixed, and stirred at 70° C. for 2 hours to obtain a lignin initiator;

[0015] Among them, the stirring speed is 150r / min;

[0016] The reaction uses sulfuric acid as a reaction catalyst, and the amount of sulfuric acid added is 5% of the mass of the organic solvent lignin;

[0017] (2) adding a silane coupling agent to ethanol, stirring and mixing for 15-20 minutes, then adding water, and continuing to stir for 30 minutes to obtain a silane coupling agent solution;

[0018] Adding nano-molybdenum disulfide to the silane coupling agent solution, keeping warm in a water bath at 60-65° C., stirring for 4 hours, then filtering, washing, and drying to obtain nano-treated molybdenum disulfide;

[0019] Among them, the drying temperature is 60°C and the time is 1 hour;

[0020] (3) lauryl methacrylate, lignin, lignin initiator, and treated nano-molybdenum disulfide are added to an organic solvent in sequence, and then the temperature is adjusted to 60°C, stirred for 10 minutes, dipyridine is added, and the reaction is continued with stirring for 20 hours, freeze-dried, and then washed with anhydrous methanol for 10 minutes, and then dried to obtain a lignin grafted product;

[0021] Among them, the freeze-drying temperature is minus 20°C;

[0022] The re-drying temperature was 60°C and the time was 1 hour.

[0023] As a further technical solution, the total molar concentration of free hydroxyl groups of the organic solvent lignin in step (1) is 4.0 mmol / g;

[0024] The molar ratio of the organic solvent lignin to 2-bromoisobutyryl bromide is 1:1.

[0025] As a further technical solution, the silane coupling agent solution in step (2) is a vinyl tris(β-methoxyethoxy)silane solution;

[0026] The mass ratio of each component is: 20% vinyl tris(β-methoxyethoxy)silane, 72% ethanol, and 8% water;

[0027] The mixing ratio of the nano-molybdenum disulfide and the silane coupling agent solution is 10-15g:100mL.

[0028] As a further technical solution, in step (3), lauryl methacrylate, lignin, lignin initiator, and treated nano-molybdenum disulfide are sequentially added to the organic solvent in a mixing ratio of 32-35 g: 3-4 g: 1-1.8 g: 10-12 g: 200 mL.

[0029] As a further technical solution, the organic solvent is a mixture of tetrahydrofuran and N,N-dimethylformamide;

[0030] The volume ratio of tetrahydrofuran to N,N-dimethylformamide is 5:1.

[0031] As a further technical solution, the calcium carbonate is heavy calcium carbonate;

[0032] The antioxidant is antioxidant 168;

[0033] The nucleating agent is methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate.

[0034] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0035] S1, mixing magnesium sulfate whiskers and fillers respectively, and then adding them into a ball mill for grinding for 25 minutes to obtain a first mixed material;

[0036] S2, adding the first mixed material, polypropylene resin, antioxidant, nucleating agent, lignin grafted material, and polyethylene wax into a high-speed mixer in sequence, stirring at 80° C. for 20 minutes to obtain a second mixed material;

[0037] Among them, the stirring speed is 2000r / min;

[0038] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0039] The drying temperature is 100°C and the drying time is 30 minutes.

[0040] As a further technical solution: the speed of ball milling in the ball mill described in step S1 is 200r / min;

[0041] As a further technical solution: the extrusion temperature of the twin-screw extruder is 190-200°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

[0042] Beneficial effects:

[0043] The plastic masterbatch prepared by the invention has excellent scratch resistance and can be applied to the field of plastic products prone to scratches to improve the service life thereof.

[0044] The invention introduces a certain amount of magnesium sulfate whiskers, and the introduction of magnesium sulfate whiskers can effectively improve the toughness and impact strength of plastic masterbatch, which is mainly because the magnesium sulfate whiskers can disperse stress impact; the introduction of lignin grafts can greatly improve the scratch resistance of plastic masterbatch, and in the preparation process of lignin grafts, nano molybdenum disulfide is introduced, and the interface bonding force between lignin grafts and polypropylene matrix resin is particularly excellent due to the small particle size and large specific surface area of ​​nano molybdenum disulfide, and the nano molybdenum disulfide can also play the role of crystallizer, which can greatly improve the crystallinity of polypropylene resin, so that the plastic masterbatch after molding is formed. The plastic product has a harder and more wear-resistant surface, thereby greatly improving the surface scratch resistance of the plastic product. Since the nanoparticles have an aggregation effect, they are easily aggregated and unevenly dispersed when directly introduced into the plastic masterbatch, which not only fails to effectively improve the scratch resistance of the plastic masterbatch, but also reduces the mechanical properties of the plastic product made of the plastic masterbatch and has a significant decreasing effect. Therefore, the present invention introduces nano-molybdenum disulfide in the preparation process of the lignin graft, and the introduction of the lignin graft can effectively solve the problem of uneven dispersion of nano-molybdenum disulfide, can be dispersed more evenly, and can further improve the comprehensive performance of polypropylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a bar graph of the scratch resistance ΔL value of the embodiments and comparative examples. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] A scratch-resistant plastic masterbatch specially used for plastics, comprising the following components by weight:

[0048] 80-90 parts of polypropylene resin, 3-5 parts of magnesium sulfate whisker, 1-3 parts of antioxidant, 1-1.8 parts of nucleating agent, 15-24 parts of filler, 5-8 parts of lignin grafted material, 2-2.5 parts of polyethylene wax;

[0049] The molecular weight of the polyethylene wax is 3500;

[0050] The filler used is calcium carbonate.

[0051] The preparation method of the lignin grafted material is as follows:

[0052] (1) First, an organic solvent lignin and 2-bromoisobutyryl bromide are mixed, and stirred at 70° C. for 2 hours to obtain a lignin initiator;

[0053] Among them, the stirring speed is 150r / min;

[0054] The reaction uses sulfuric acid as a reaction catalyst, and the amount of sulfuric acid added is 5% of the mass of the organic solvent lignin;

[0055] (2) adding a silane coupling agent to ethanol, stirring and mixing for 15-20 minutes, then adding water, and continuing to stir for 30 minutes to obtain a silane coupling agent solution;

[0056] Adding nano-molybdenum disulfide to the silane coupling agent solution, keeping warm in a water bath at 60-65° C., stirring for 4 hours, then filtering, washing, and drying to obtain nano-treated molybdenum disulfide;

[0057] Among them, the drying temperature is 60°C and the time is 1 hour;

[0058] (3) lauryl methacrylate, lignin, lignin initiator, and treated nano-molybdenum disulfide are added to an organic solvent in sequence, and then the temperature is adjusted to 60°C, stirred for 10 minutes, dipyridine is added, and the reaction is continued with stirring for 20 hours, freeze-dried, and then washed with anhydrous methanol for 10 minutes, and then dried to obtain a lignin grafted product;

[0059] Among them, the freeze-drying temperature is minus 20°C;

[0060] The re-drying temperature was 60°C and the time was 1 hour.

[0061] The total molar concentration of free hydroxyl groups of the organic solvent lignin in step (1) is 4.0 mmol / g;

[0062] The molar ratio of the organic solvent lignin to 2-bromoisobutyryl bromide is 1:1.

[0063] In step (2), the silane coupling agent solution is a vinyl tris(β-methoxyethoxy)silane solution;

[0064] The mass ratio of each component is: 20% vinyl tris(β-methoxyethoxy)silane, 72% ethanol, and 8% water;

[0065] The mixing ratio of the nano-molybdenum disulfide and the silane coupling agent solution is 10-15g:100mL.

[0066] In step (3), lauryl methacrylate, lignin, lignin initiator, and treated nano-molybdenum disulfide are sequentially added to the organic solvent in a mixing ratio of 32-35 g: 3-4 g: 1-1.8 g: 10-12 g: 200 mL.

[0067] The organic solvent is a mixture of tetrahydrofuran and N,N-dimethylformamide;

[0068] The volume ratio of tetrahydrofuran to N,N-dimethylformamide is 5:1.

[0069] Calcium carbonate is heavy calcium carbonate;

[0070] The antioxidant is antioxidant 168;

[0071] The nucleating agent is methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate.

[0072] Example 1

[0073] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0074] S1, 3g of magnesium sulfate whisker and 15g of heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0075] S2, adding the first mixed material, 80 g of polypropylene resin, 1 g of antioxidant 168, 1 g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, 5 g of lignin grafted material, and 2 g of polyethylene wax into a high-speed mixer in sequence, stirring at 80° C. for 20 min to obtain a second mixed material;

[0076] Among them, the stirring speed is 2000r / min;

[0077] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0078] The drying temperature is 100°C and the drying time is 30 minutes. The extrusion temperature of the twin-screw extruder is 190°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

[0079] Example 2

[0080] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0081] S1, 3.5g magnesium sulfate whisker and 18g heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0082] S2, adding the first mixture, 85g of polypropylene resin, 2g of antioxidant 168, 1.3g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, 6g of lignin grafted material, and 2.1g of polyethylene wax into a high-speed mixer in sequence, stirring at 80°C for 20min to obtain a second mixture;

[0083] Among them, the stirring speed is 2000r / min;

[0084] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0085] The drying temperature is 100°C and the drying time is 30 minutes. The extrusion temperature of the twin-screw extruder is 195°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

[0086] Example 3

[0087] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0088] S1, 4g of magnesium sulfate whisker and 20g of heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0089] S2, adding the first mixture, 85g of polypropylene resin, 2g of antioxidant 168, 1.4g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, 6g of lignin grafted material, and 2.3g of polyethylene wax into a high-speed mixer in sequence, stirring at 80°C for 20min to obtain a second mixture;

[0090] Among them, the stirring speed is 2000r / min;

[0091] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0092] The drying temperature was 100°C and the drying time was 30 minutes. The extrusion temperature of the twin-screw extruder was 195°C, the main engine speed was 350rpm, the feeding speed was 55rpm, and the pelletizer speed after extrusion was 50rpm.

[0093] Example 4

[0094] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0095] S1, 4g of magnesium sulfate whisker and 22g of heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0096] S2, adding the first mixed material, 88 g of polypropylene resin, 2 g of antioxidant 168, 1.5 g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, 7 g of lignin grafted material, and 2.2 g of polyethylene wax into a high-speed mixer in sequence, stirring at 80° C. for 20 min to obtain a second mixed material;

[0097] Among them, the stirring speed is 2000r / min;

[0098] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0099] The drying temperature was 100°C and the drying time was 30 minutes. The extrusion temperature of the twin-screw extruder was 195°C, the main engine speed was 350rpm, the feeding speed was 55rpm, and the pelletizer speed after extrusion was 50rpm.

[0100] Example 5

[0101] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0102] S1, 5g of magnesium sulfate whisker and 24g of heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0103] S2, adding the first mixture, 90g of polypropylene resin, 3g of antioxidant 168, 1.8g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, 8g of lignin grafted material, and 2.5g of polyethylene wax into a high-speed mixer in sequence, stirring at 80°C for 20min to obtain a second mixture;

[0104] Among them, the stirring speed is 2000r / min;

[0105] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0106] The drying temperature is 100°C and the drying time is 30 minutes. The extrusion temperature of the twin-screw extruder is 200°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

[0107] Comparative Example 1:

[0108] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0109] S1, 3g of magnesium sulfate whisker and 15g of heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0110] S2, adding the first mixed material, 80 g of polypropylene resin, 1 g of antioxidant 168, 1 g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, and 2 g of polyethylene wax into a high-speed mixer in sequence, stirring at 80° C. for 20 min to obtain a second mixed material;

[0111] Among them, the stirring speed is 2000r / min;

[0112] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0113] The drying temperature is 100°C and the drying time is 30 minutes. The extrusion temperature of the twin-screw extruder is 190°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

[0114] Comparative Example 2:

[0115] A method for preparing a scratch-resistant plastic masterbatch for plastics, comprising the following steps:

[0116] S1, 3g of magnesium sulfate whisker and 15g of heavy calcium carbonate were mixed respectively, and then added into a ball mill for grinding for 25min to obtain a first mixed material; the speed of ball milling in the ball mill was 200r / min;

[0117] S2, adding the first mixed material, 80 g of polypropylene resin, 1 g of antioxidant 168, 1 g of methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate, 5 g of lignin, and 2 g of polyethylene wax into a high-speed mixer in sequence, stirring at 80° C. for 20 min to obtain a second mixed material;

[0118] Among them, the stirring speed is 2000r / min;

[0119] S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics;

[0120] The drying temperature is 100°C and the drying time is 30 minutes. The extrusion temperature of the twin-screw extruder is 190°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

[0121] test:

[0122] The masterbatches of the embodiment and the comparative example were processed into test specimens with the same specifications by an injection molding machine under the same conditions and parameters for testing:

[0123] The scratch resistance test of the embodiment and the comparative example samples was carried out according to the standard PV3952, the test load was 10N, and the scratch resistance performance was evaluated by measuring the ΔL value (i.e. the change mark of black and white color) on the surface of the scratched sample;

[0124] The smaller the ΔL value, the better the scratch resistance of the material:

[0125] Table 1

[0126]

[0127]

[0128] It can be seen from Table 1 that the plastic masterbatch prepared in the example has excellent scratch resistance.

[0129] Taking Example 1 as the basic sample, the effects of different amounts of lignin grafted material added on the scratch resistance of the sample strips were compared:

[0130] Table 2

[0131] Addition amount / g ΔL value 0 0.98 3 0.63 5 0.28 7 0.27 9 0.28 11 0.28 13 0.29

[0132] It can be seen from Table 2 that with the increase in the amount of lignin grafted material added, the scratch resistance of the plastic first increases and then tends to remain unchanged.

[0133] The hardness of the test samples of the above embodiments and comparative examples was tested according to ASTM D-785:

[0134] Table 3

[0135] Rockwell hardness Example 1 100 Example 2 102 Example 3 99 Example 4 101 Example 5 100 Comparative Example 1 90 Comparative Example 2 91

[0136] It can be seen from Table 3 that the plastic parts processed from the plastic masterbatch prepared in the present invention have higher surface hardness, and the scratch resistance of the plastic can be effectively improved by improving the hardness.

[0137] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A scratch-resistant plastic masterbatch for plastics, characterized in that: By weight Includes the following ingredients: 80-90 parts of polypropylene resin, 3-5 parts of magnesium sulfate whisker, 1-3 parts of antioxidant, 1-1.8 parts of nucleating agent, 15-24 parts of filler, 5-8 parts of lignin grafted material, 2-2.5 parts of polyethylene wax; The polyethylene wax has a molecular weight of 3500; The filler is calcium carbonate; The preparation method of the lignin grafted material is as follows: (1) First, an organic solvent lignin and 2-bromoisobutyryl bromide are mixed, and stirred for reaction at 70° C. for 2 hours to obtain a lignin initiator; the total mass molar concentration of free hydroxyl groups in the organic solvent lignin is 4.0 mmol / g; and the molar ratio of the organic solvent lignin to 2-bromoisobutyryl bromide is 1:1; Among them, the stirring speed is 150r / min; The reaction uses sulfuric acid as a reaction catalyst, and the amount of sulfuric acid added is 5% of the mass of the organic solvent lignin; (2) Add the silane coupling agent to ethanol, stir and mix for 15-20 minutes, then add water and continue stirring for 30 minutes to obtain a silane coupling agent solution; Adding nano-molybdenum disulfide to the silane coupling agent solution, keeping warm in a water bath at 60-65° C., stirring for 4 hours, then filtering, washing, and drying to obtain nano-treated molybdenum disulfide; Among them, the drying temperature is 60°C and the time is 1 hour; The silane coupling agent solution is vinyl tris (β-methoxyethoxy) silane solution; The mass ratio of each component of the silane coupling agent solution is: 20% vinyl tri(β-methoxyethoxy) silane, 72% ethanol, and 8% water; The mixing ratio of the nano-molybdenum disulfide and the silane coupling agent solution is 10-15g:100mL; (3) Add lauryl methacrylate, lignin, lignin initiator, and treated nano-molybdenum disulfide to an organic solvent in sequence, then adjust the temperature to 60°C, keep stirring for 10 minutes, add dipyridine, continue stirring and reacting for 20 hours, freeze-dry, and then wash with anhydrous methanol for 10 minutes, and then dry to obtain a lignin grafted product; lauryl methacrylate, lignin, lignin initiator, and treated nano-molybdenum disulfide are added to the organic solvent in sequence in a mixing ratio of: 32-35g: 3-4g: 1-1.8g: 10-12g: 200mL; Among them, the freeze-drying temperature is minus 20°C; The re-drying temperature was 60°C and the time was 1 hour.

2. The scratch-resistant plastic masterbatch for plastics according to claim 1, characterized in that: The organic solvent is a mixture of tetrahydrofuran and N,N-dimethylformamide; The volume ratio of tetrahydrofuran to N,N-dimethylformamide is 5:

1.

3. The scratch-resistant plastic masterbatch for plastics according to claim 1, characterized in that: The calcium carbonate is heavy calcium carbonate; The antioxidant is antioxidant 168; The nucleating agent is methylene bis(2,4-di-tert-butylphenoxy)aluminum phosphate.

4. The method for preparing a scratch-resistant plastic masterbatch for plastics according to claim 1, characterized in that: The following steps are involved: S1, mixing magnesium sulfate whiskers and fillers respectively, and then adding them into a ball mill for grinding for 25 minutes to obtain a first mixed material; S2, adding the first mixed material, polypropylene resin, antioxidant, nucleating agent, lignin grafted material, and polyethylene wax into a high-speed mixer in sequence, stirring at 80° C. for 20 minutes to obtain a second mixed material; Among them, the stirring speed is 2000r / min; S3, adding the second mixed material into a twin-screw extruder for blending and extrusion, pelletizing, and then drying to obtain a scratch-resistant plastic masterbatch for plastics; The drying temperature is 100°C and the drying time is 30 minutes.

5. The method for preparing a scratch-resistant plastic masterbatch for plastics according to claim 4, characterized in that: The rotation speed of ball milling in the ball mill described in step S1 is 200 r / min.

6. The method for preparing a scratch-resistant plastic masterbatch for plastics according to claim 4, characterized in that: The extrusion temperature of the twin-screw extruder is 190-200°C, the main engine speed is 350rpm, the feeding speed is 55rpm, and the pelletizer speed after extrusion is 50rpm.

Citation Information

Patent Citations

  • Transparent flame-retardant plastic master batch and preparation method thereof

    CN112521689A

  • Degradable lignin grafted polylauryl methacrylate-low density polyethylene composite material and preparation method thereof

    CN113801423A

  • Modified PP (polypropylene) material as well as preparation method and application thereof

    CN114591564A

  • Modified polypropylene composite material and preparation method thereof

    CN116640383A